On the translaminar fracture toughness of Vectran/epoxy composite material. (15th October 2018) - Abdullah, S.I.B. Syed; Iannucci, L.; Greenhalgh, E.S.
Abstract: The mode I fracture toughness associated with fibre tensile failure was investigated for a Vectran/MTM57 composite system. A modified compact tension specimen was designed and manufactured to mitigate compressive and buckling failure due to the low compressive properties which are an inherent characteristic of Vectran fibres. On average, the mode I translaminar fracture toughness for Vectran/MTM57 was found to be approximately 130–145 kJ/m 2 for initiation and 250–260 kJ/m 2 for propagation. In contrast with other composite systems such as carbon and glass fibre, the fracture toughness of Vectran/MTM57 was found to be relatively higher, with up to 48.26% and 95.27% for initiation and propagation, respectively for some carbon fibre composite system; 9.93% and 68.6% for initiation and propagation, respectively for S2-Glass/epoxy system.